Performance of mortar with egg albumen - Yong, Sharon Wen Tin (2010)
This study is to investigate the performance of mortar with 1% and 5% egg albumen. The field of studies covered the important parameters in determining the engineering properties such as compressive and flexural strength and drying shrinkage of egg albumen additive in mortar. It was achieved by compression test and flexural test conducted to determine the highest strength development between samples for 7, 14 and 28 age days of both air and water curing time. There were three types of samples That has been tested, which are mortar containing 1% of egg albumen, 5% of egg albumen and mortar with plain ordinary Portland cement as the control samples. The result obtained showed that the compressive strength for water curing for 100% mortar control samples achieved the highest strength where is it 5.78Mpa and it is 3.58% higher strength than the air cured samples, while mortar with 5% egg albumen achieved 5.02Mpa of strength where it is 9.37% higher than sir cured samples. Next it is mortar with 1% egg albumen that achieved 4.64Mpa where it is only 4.71% higher than air cured samples. For flexural test, the result obtained where mortar with 5% egg albumen achieved the highest flexural strength for water cured samples where it is 36.27% higher than the air cured samples, while for mortar with 1% egg albumen has achieved flexural strength of 2.4Mpa for air cured samples, where it is 20.6% higher than the water cured samples. As for 100% mortar control samples has achieved the lowest strength, where it is 1,98Mpa for air cured samples. As for the result achieved from drying shrinkage test, result obtained for air cured samples achieves highest shrinkage if compared with water cured samples. The used of concrete as samples besides mortar is recommended for future works and studies.